Hotel Attributes Influencing International Tourists’ Satisfaction and Loyalty - Baniya, Rojan; Thapa, Prajwal (Journal of Tourism and Hospitality Education, 2017)
This study investigates the influence of hotel attributes on satisfaction of 119 international tourists visiting to Nepal. It further analyzes the effect of satisfaction from hotels on revisit intention and recommendations by international tourists. 119 international tourists visiting to Nepal participated in the study. Correlation and multiple regression analyses were conducted to test hypotheses. Our result shows that among various hotel attributes, service quality and room & front desks plays significant role in satisfaction of international tourists. The other attributes like security, business facility, value, food and recreation and security were found to beinsignifi cant. Furthermore, satisfaction was found to be Significant predictor of both attitudinal loyalty i.e. intentional loyalty and behavioral loyalty i.e. revisit intention. There are lots of practical and research implications of the findings like it’s a lesson for Nepal Tourism Board, Hotel Association of Nepal and other related stakeholders. It guides them as where to focus their energy in terms of generating satisfaction and loyalty from international tourists in case of hotel service. Journal of Tourism and Hospitality EducationVol. 7, 2017, page : 44-61